PENGARUH MODEL PEMBELAJARAN VAK (VISUALISASI, AUDITORI, KINESTETIK) TERHADAP PRESTASI BELAJAR PAI PADA SISWA DI SDN TLOGOMULYO TEMANGGUNG - Kartika Hartanti (Jurnal Pendidikan Agama Islam, 2014)
This study aims to determine the effect of the application of VAK learning model on the learning achievement of PAI in class V Tlogomulyo Waterford Elementary School. This study was a quasi-experimental study (quasi-experimental). Subjects in this study consisted of 26 students of class V. The data was collected using VAK learning guidelines, test learning Islamic education, observation, documentation, and interviews. The validity of the instrument showing of 10 items proved to be valid all, are the results of the analysis show the reliability coefficient of 0.710 and otherwise reliable. Analysis of the data used in the form of comparative analysis using t-test. The results showed that there are significant implementation VAK learning model significantly to the learning outcomes of Islamic education. It can be seen from the difference in learning achievement Islam shortly before and after the given method VAK, the t value of 0.828 and significance level (p) of 0.05. In addition, an increase in the average acquisition value before application of VAK learning model (pre-test = 71.9) and after application of VAK learning model (post-test = 87.3). This shows an increase in the average value of 15.4. By looking at the difference in the score of the pre test and post test, shows that the VAK learning model is a model of effective learning for learning PAI.